(untitled) (NPRC Journal of Multidisciplinary Research, 2025)
This study examines Dalit caste discrimination in the urban setting of Kirtipur, Kathmandu, Nepal, through a quantitative-dominant mixed approach. The researcher conducted a questionnaire survey of 134 respondents, 85 of whom were temporary students residing in Kirtipur for study purposes and 49 local students who were permanent residents. The findings of the quantitative study were further triangulated with qualitative assessment by employing purposively selected four Key informant interviews. The study’s findings indicate that caste discrimination among Dalits is a structural issue, but attitudes are changing due to increased awareness and education. Nepali society, mainly urban areas, has massive mobility of people from different castes/ethnicities, and those regions are undergoing rapid sociocultural changes. Caste issues among the students have been diluted from extreme worldviews, but they are facing to penetrate the mainstream social order of society. While discrimination is rare among educated people, such as students, problems persist in rural and underdeveloped areas. Although policy reforms are in place, social behavioural changes remain crucial for achieving equality. The study’s findings have significant implications for policy and further research, highlighting the need for continued social behavioural changes and further studies in this regard.